Improvement of an automated CAN packaging system based on modeling and analysis approach through robot simulation tools - Srasrisom, Khongsak; Srinoi, Pramot; Chaijit, Seksan; Wiwatwongwana, Fasai (IAES International Journal of Robotics and Automation (IJRA), 2020)
The application of robot simulation tools for modelling, analysis and improvement of existing industrial manufacturing cells is presented with reference to the development and implementation of the digital factory concept. A real case study of aerosol can packaging and palletizing cell scenario in the metal can manufacturing industry for containing food and products is used as a reference in this paper. For studying manual aerosol can packaging and palletizing conditions of the worker, a detailed time and motion analysis of workers is carried out. On the basis of cycle time analysis results, an alternative to the manual operation, a more sophisticated automated packaging and palletizing system is suggested. A proposed system which uses a robotic manipulator including automated production machine and devices are also developed and tested. The viability of the suggested system is checked through simulation and cycle time analysis. A fuzzy logic software, MATLAB is employed in order to analyse the actual system’s behaviour in terms of productivity, and utilization of the available facilities. The 3D simulation software, DELMIA V6  is additionally employed to perform a detailed design phase of the manufacturing cell. From the simulation results, this gives a rough approximation that the production of one robotized manipulator, and automated packaging and palletizing cell is equal to the production of about 4.3 manual packaging and palletizing cells. These results have shown the need for change to automation in the aerosol can packaging and palletizing system.